2012
DOI: 10.1016/j.neuroimage.2011.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal loss of gray matter volume in patients with first-episode schizophrenia: DARTEL automated analysis and ROI validation

Abstract: Region of Interest (ROI) longitudinal studies have detected progressive gray matter (GM) volume reductions in patients with first-episode schizophrenia (FESZ). However, there are only a few longitudinal voxel-based morphometry (VBM) studies, and these have been limited in ability to detect relationships between volume loss and symptoms, perhaps because of methodologic issues. Nor have previous studies compared and validated VBM results with manual Region of Interest (ROI) analysis. In the present VBM study, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 62 publications
9
101
1
2
Order By: Relevance
“…In addition, our findings of progressive loss in cortical and cerebral GM volume, cortical thinning, and increases in V3 volume are consistent with previous findings. 1,[3][4][5][6] Unlike previous studies, [3][4][5] we did not find significant volume or thickness loss in frontal regions. Possible reasons for the discrepancy include a longer duration of the illness or more severe symptoms in the patient samples included in those studies.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In addition, our findings of progressive loss in cortical and cerebral GM volume, cortical thinning, and increases in V3 volume are consistent with previous findings. 1,[3][4][5][6] Unlike previous studies, [3][4][5] we did not find significant volume or thickness loss in frontal regions. Possible reasons for the discrepancy include a longer duration of the illness or more severe symptoms in the patient samples included in those studies.…”
Section: Discussioncontrasting
confidence: 93%
“…6,7 These brain changes appear to be clinically relevant because they are linked to outcome, 4,5,8 although confounding effects of antipsychotic medications cannot be ruled out. [9][10][11][12] Schizophrenia is characterized by global cognitive impairments 13 and deficits in specific domains, such as verbal, memory, and executive functioning.…”
mentioning
confidence: 99%
“…Therefore, hypoxia can cause changes to the VEGF signaling pathway during early development leading to changes in blood flow and brain volume as seen in individuals with schizophrenia [16,17]. In this regard, studies have shown that rodents exposed to hypoxia incur anatomical changes relevant to schizophrenia in adult offspring [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation of anatomical and functional alterations might result from the different analysis methods, which measure different aspects of gray matter in schizophrenia. In the present study, VBM measures GMV changes which are stable and long-standing (Chan et al, 2011;Asami et al, 2012). On the contrary, functional alterations measured by fALFF may represent physiological changes in acute stage of disease .…”
Section: Discussionmentioning
confidence: 75%